Report on the Measurement of International Capital Flows. (International Monetary Fund, 1992)
The Report evaluates statistical practices relating to the measurement of international capital flows. In particular, the principal sources of statistical descrepancies in the component categories of the capital account in the global balance of payments are addressed.